A systematic optimization procedure of antenna miniaturization for efficient wireless energy transfer - Mohamad Harris Misran; Sharul Kamal Abdul Rahim; Maizatul Alice Meor Said; Mohd Azlishah Othman (Institute of Advanced Engineering and Science, 2019)
This paper presents a systematic optimization procedure to determine the reduced antenna size aimed at obtaining the best efficiency or at least equal performance with the initial large antenna design in a wireless energy transfer (WET) system. A low-cost, square-shaped planar loop antenna designed on each side of FR4 substrate is used as both the miniature transmitter and receiver antennas operating at 13.56 MHz for the near-field communication (NFC) band. The effect of distance and antenna size on the link parameters such as inductance, resistance and mutual coupling is studied, prior to the study of their effects on WTE. The accuracy of the procedure is cross-validated using two methods; analytically and using full wave simulations. The simulation then is verified using lab measurement setup at real scene environment. Trends of the resulting curves using both methods indicated good agreements, and optimal miniature antenna for the best wireless transfer efficiency (WTE) is able to be quickly determined. A miniature antenna is able to achieve 4% wireless transfer efficiency improvement with 47% antenna size reduction. Such method can be applied to efficiently estimate a low-cost WTE system setup, besides enabling the integration of self-tuning or reconfigurability features in such systems for a known initial antenna size to mitigate changes to its operating distance.